1975
DOI: 10.1093/geronj/30.5.601
|View full text |Cite
|
Sign up to set email alerts
|

Housing Characteristics and the Well-Being of Elderly Tenants in Federally Assisted Housing

Abstract: The relationship between sponsorship, community size, building size (number of dwelling units) and height of building, on the one hand, and six indices of well-being of elderly tenants, on the other, was examined in a study of 2457 subjects from 154 federally-assisted housing projects. Control was exercised on a variety of personal variables prior to the examination of the environmental relationships to well-being. Private nonprofit sponsorship was associated with higher friendship scores and greater activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Each scale item is rated on a 7-point scale from strongly disagree (1) to strongly agree (7), with higher scores representing greater life satisfaction. In a review of SWLS research, Pavot and Diener (12) suggested that the measure successfully detects change in life satisfaction over time and the course of clinical interventions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each scale item is rated on a 7-point scale from strongly disagree (1) to strongly agree (7), with higher scores representing greater life satisfaction. In a review of SWLS research, Pavot and Diener (12) suggested that the measure successfully detects change in life satisfaction over time and the course of clinical interventions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the earlier social psychological literature would suggest that QOL as a global construct, rather than reflecting health status constructs, is represented by an overall satisfaction, or happiness, with one’s life (6,7). Physical functioning and physical health status variables are more proximal indicators of overall QOL (8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the elderly in high rises versus low rises have produced mixed results. A nationwide U.S. study of the elderly found that residents of low buildings liked their housing more than residents of taller buildings, although the magnitude of this effect was quite small (Lawton, Nahemow & Teaff, 1975). A much smaller study of elderly persons who were randomly assigned to high-and low-rises reported a small difference in morale that favoured high rises over low rises (Duffy & Willson, 1984).…”
Section: Residential Satisfaction and Preferences In High-rise Buildingsmentioning
confidence: 98%
“…Within this body of research, size of the housing unit and the subjective or psychological value of the home have emerged as central determinants of housing satisfaction among the elderly. Overly large dwelling structures are associated with dissatisfaction in private (Lawton et al, 1978) as well as public housing (Lawton et a]., 1975). The presence of central heating and a modem structure (Lawton, 1980b) as well as a perceived ambience or pleasantness of a dwelling unit (Lawton et al, 1978) promote satisfaction with housing.…”
Section: Journal Of Housing For the Elderlymentioning
confidence: 99%